Balanced Column-Wise Block Pruning for Maximizing GPU Parallelism - Park, Cheonjun; Park, Mincheol; Oh, Hyun Jae; Kim, Minkyu; Yoon, Myung Kuk; Kim, Suhyun; Ro, Won Woo (Proceedings of the AAAI Conference on Artificial Intelligence, 2023)
Pruning has been an effective solution to reduce the number of computations and the memory requirement in deep learning.The pruning unit plays an important role in exploiting the GPU resources efficiently. The filter is proposed as a simple pruning unit of structured pruning.However, since the filter is quite large as pruning unit, the accuracy drop is considerable with a high pruning ratio.GPU rearranges the weight and input tensors into tiles (blocks) for efficient computation. To fully utilize GPU resources, this tile structure should be considered, which is the goal of block pruning. However, previous block pruning prunes both row vectors and column vectors. Pruning of row vectors in a tile corresponds to filter pruning, and it also interferes with column-wise block pruning of the following layer.In contrast, column vectors are much smaller than row vectors and can achieve lower accuracy drop.Additionally, if the pruning ratio for each tile is different,GPU utilization can be limited by imbalanced workloads by irregular-sized blocks.The same pruning ratio for the weight tiles processed in parallel enables the actual inference process to fully utilize the resources without idle time.This paper proposes balanced column-wise block pruning, named BCBP, to satisfy two conditions: the column-wise minimal size of the pruning unit and balanced workloads. We demonstrate that BCBP is superior to previous pruning methods through comprehensive experiments.